Task Content and Job Losses in the Great Lockdown - Petroulakis, Filippos (Industrial & labor relations review, 2023)
The author examines the short-term labor market effects of the COVID-19 pandemic (aka the Great Lockdown recession) in the United States. Findings show that the task content is an important predictor of job losses; jobs with a high non-routine cognitive content are especially well-protected, even if they are not teleworkable. Teleworkability matters more for low-paying jobs. The importance of task content, particularly for non-routine cognitive tasks, is strong even after controlling for demographics and for differential sector and location shocks, while effects persist in the medium run. Jobs subject to higher structural turnover rates were much more likely to be terminated, suggesting that easier-to-replace employees were at a particular disadvantage, even within sectors. At the same time, labor hoarding may occur for more valuable matches. Individuals in low-skilled jobs fared comparatively better in industries with a high share of high-skilled workers, suggesting complementarities across skill types.